DESENVOLVIMENTO DA COCHONILHA-BRANCA PLANOCOCCUS CITRI (RISSO, 1813) (HEMIPTERA: PSEUDOCOCCIDAE) EM FRUTÍFERAS - Correa, L.r.b. [UNESP]; Souza, B.; Santa-cecília, L.v.c. (Instituto Biológico, 2021)
The citrus mealybug, Planococcus citri is an important pest attacking several crops. Biotic and abiotic factors, as well as the substrate they feed on influence its population. The present study was aimed to study the effect of some feeding substrates on mealybug development in laboratory conditions. Leaf disks of guava, fig and cherimoya were placed individually on an agar film inside a Petri dish. One egg of the insect was confined inside each container, replicated 60 times for each treatment. Containers were kept in a climatized chamber at 25º C, 70 ± 10% RH and 12 hours photophase. Insects reared on guava leaves showed a longer nymphal development, while the female longevity was longer on fig leaves. However, no statistical differences were found in the survival index, which showed values higher than 83%, suggesting that all substrates studied here were adequate for the development of P. citri.

A cochonilha-branca, Planococcus citri, constitui-se em uma importante praga em diversas culturas, sendo suas populações influenciadas por vários fatores bióticos e abióticos. Considerando-se a diversidade de hospedeiros que podem ser infestados, bem como a escassez de informações sobre seu desenvolvimento, esse trabalho objetivou estudar alguns aspectos da biologia de P. citri criada em três substratos alimentares. Ovos de P. citri, em número de 60, foram individualizados em placas de Petri contendo discos foliares de goiabeira (Psidium guajava L.) variedade Paluma, figueira (Ficus carica L.) variedade Roxo de Valinhos e gravioleira (Annona muricata L.) variedade Lisa, dispostos sobre uma lâmina de ágar-água a 1%. As placas foram vedadas com filme plástico PVC e mantidas em câmara climatizada a 25ºC, 70±10% UR e 12 horas de fotofase. Os substratos alimentares influenciaram a duração do período ninfal e longevidade de fêmeas e machos. A goiabeira proporcionou maior duração do período ninfal e a figueira maior longevidade das fêmeas. A sobrevivência em cada ínstar e no período ninfal não diferiu em função dos substratos avaliados, os quais proporcionaram viabilidades superiores a 83%, constituindo-se em hospedeiros adequados para o desenvolvimento de P. citri.
DEVELOPMENT OF THE CITRUS MEALYBUG PLANOCOCCUS CITRI (RISSO, 1813) (HEMIPTERA: PSEUDOCOCCIDAE) ON DIFFERENT FRUIT-BEARING PLANTS
Keywords: Food substrates; guava; cherimoya; fig; pseudococcids; biology; Substratos alimentares; goiabeira; gravioleira; figueira; pseudococídeo; biologia